Design and Performance Test of Axial Halbach Brushless DC Motor with Power Density 1.5 Kw/Kg - Kevin Dwi Prasetio; Muhammad Nur Yuniarto (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2016)
Progress of technology on electric vehicle component sector is one reason the emergence of electric vehicles at the moment. Starting from battery which has a great current density up to the automatic control systems on electric vehicles. But there are still some shortcomings of this electric vehicle components, one of which is the low value of power density of existing electric motor in the market today.On vehicles such as electric cars when Race Car Contest, energy saving problems about power density of the driving motor is very vital. This is because the total weight of the vehicle has a huge influence on the vehicle efficiency is against it. The issue is one of the reasons of the research task. In this final task is done making the design, simulation, and architecture of the Axial Halbach Brushless DC Motor. Use of system configuration on the halbach magnet to avoid the use of iron as a material cantilever rotor. By changing the material of the cantilever rotor with lighter materials such as aluminum or even carbon fibre, the value of power density electric motors can be increased. Then using the litz wire on coil stator to reduce loss-power loss due to the barriers on the coil. Coreless stator on the system and to avoid the phenomenon of cogging at the time due to low rpm style attraction magnet with iron in the core material. While the creation process begins by determining the specifications of the Axial Halbach Brushless DC motors. Then go into the design phase of the mechanical and electrical design. Who then conducted simulations to help determine other parameters such as air gap, slot turn, and magnetic orientation. The process of making a component of stator and rotor after the simulation is completed. After all the components of the rotor and stator on assembly, mounting the hall sensor is carried out to the right to position obtained by reading the signals. After the motor can spin with good motor performance, testing can be done. This final task generates Axial Halbach Brushless DC Motor with construction of one rotor and a stator. Axial DC Brushless Halbach Motor consists of 10 pole halbach magnet system permanent and 30 slot on the stator. On the performance test of Axial Halbach Brushless DCMotor it obtained efficiency of 92.72%, power output of 807.34 Watts, torque of 2.24 Nm, moment rpm 3451. As well as the power density of 0.588 kW/kg at 50% throttle openings